DESIGN THINKING APPROACH TO ENHANCE STUDENTS CREATIVITY IN SECOND LANGUAGE WRITING PERFORMANCE - Etika Ariyani , (Journal of Innovation Research and Knowledge, 2024)
This study aims to find out the effect of using design thinking approach on students creativity in write descriptive text. Design thinking approach creates collaboration, creativity and innovation. It arouses a mindset focus from problem to solution, exploring innovation and developing creativity significantly . This research was conducted by using experimental research design. The population was 2nd gr of Junior High Students. The samples of the research were divided into two classes which consisted of experimental and control group. It chosen by using random sampling method. The experimental group was taught by using collaborative learning method while the control group was taught by using conventional method. Data collected by test, test to write descriptive texts completely. After analysing the data, it was found that the value of t-observed was 5.61 with the degree of freedom 40 at the level of significance 1.764, it means that t-observed was higher that t-table (5.61>1.764). The result of this investigation showed that there are significant changes on students descriptive text, that finding explained that design thinking approach effective to enhance the students creativity in second language writing performance significantly.